Chemotherapeutic effects of doxorubicin loaded PEG coated TiO nanocarriers on breast cancer cell lines - Tas, Ayca; Kekliklicioglu Cakmak, Nese; Gumus, Erkan; Atabey, Mustafa; Silig, Yavuz (Annals of Medical Research, 2021)
None